Combustion behavior of KOH desulphurized coals assessed by TGA-DTG. Issue 20 (18th October 2018) - Ken, Bhupendra Singh; Aich, Subhajit; Saxena, V. K.; Nandi, Barun Kumar
ABSTRACT: This work presents the results obtained from the experimental study on the effects of KOH treatment and its combustion behavior of high sulfur Indian coal. Coal was treated with 5–20% KOH (v/v) concentration for 6–24 h reaction time to identify the effects of KOH treatment on coal properties. Experimental results showed that upto 36.79% of total sulfur can be removed from coal with 20% KOH concentration and 24 h contact time at atmospheric condition. However, gross calorific value of coal decreased from 6800 to 6084 kcal/kg due to removal of combustibles from coal. Combustion characteristics of treated coal were assessed by Thermo-gravimetric analysis/ Differential thermo-gravimetric (TGA/DTG analysis). Further various combustion kinetic parameters like ignition temperature, peak temperature, burnout temperature, activation energy (E), and pre-exponential factor (A) are estimated. Experimental results show that the ignition temperature of coal decreased from 321°C to 252°C, peak temperature decreased from 459°C to 409°C due to changes in the coal matrix after desulfurization. The activation energy of coal calculated decreased from 79 to 45 kJ/mol due to desulfurization using 20% KOH concentration and 24 h reaction time.